2006
DOI: 10.1002/jcb.20986
|View full text |Cite
|
Sign up to set email alerts
|

CDC2L5, a Cdk‐like kinase with RS domain, interacts with the ASF/SF2‐associated protein p32 and affects splicing in vivo

Abstract: The human CDC2L5 gene encodes a protein of unknown physiological function. This protein is closely related to the cyclin-dependent kinase (Cdks) family and contains an arginine/serine-rich (RS) domain. The Cdks were first identified as crucial regulators of cell-cycle progression, more recently they were found to be involved in transcription and mRNA processing. RS domains are mainly present in proteins regulating pre-mRNA splicing, suggesting CDC2L5 having a possible role in this process. In this study, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
76
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 43 publications
(56 reference statements)
4
76
0
Order By: Relevance
“…8). Expression of active CDK11 p110WT caused a slight change in E1A splice site usage resulting in the production of more 9S transcript, although this effect was less than the 2-3-fold increases in 9S seen following CDK12 and CDK13 expression (2)(3)(4). On the other hand, expression of inactive CDK11 p110DN decreased production of the 9S splice form and considerably increased 13 and 11S splice form levels, an effect similarly observed when endogenous CDK12 expression was decreased using RNA interference (2).…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…8). Expression of active CDK11 p110WT caused a slight change in E1A splice site usage resulting in the production of more 9S transcript, although this effect was less than the 2-3-fold increases in 9S seen following CDK12 and CDK13 expression (2)(3)(4). On the other hand, expression of inactive CDK11 p110DN decreased production of the 9S splice form and considerably increased 13 and 11S splice form levels, an effect similarly observed when endogenous CDK12 expression was decreased using RNA interference (2).…”
Section: Discussionmentioning
confidence: 79%
“…Finally, we demonstrate that expression of cyclins L␣ and -␤ and CDK11 p110 strongly and differentially affects alternative splicing in vivo. Together, these data establish that CDK11 p110 interacts physically and functionally with cyclin L␣ and -␤ isoforms and SR proteins to regulate splicing.It has become apparent over the past decade that several cyclin-dependent kinases (CDKs) 4 and their cyclin regulatory partners participate in regulating mRNA production (1). Thus far, CDK7, CDK8, and CDK9 functions are ascribed to transcriptional initiation and elongation, and CDK12 (CrkRS) and CDK13 (CDC2L5) functions are related to pre-mRNA splicing (2-4).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Neverthless, emerging evidence has shown that CDK12 contains the arginine/serine domain and is involved in RNA processing (32,33). In addition, CDK12 has been implicated in mRNA splicing (15,34,35). However, from our data, we cannot exclude the possibility that the arginine/serine domain of CDK12 also contributes to heterochromatin remodeling.…”
Section: Discussionmentioning
confidence: 99%